2018
DOI: 10.1007/s13355-018-0568-6
|View full text |Cite
|
Sign up to set email alerts
|

Existence of two strains of Habrobracon hebetor (Hymenoptera: Braconidae): a complex in Thailand and Japan

Abstract: Habrobracon hebetor Say (Hymenoptera: Braconidae) is a cosmopolitan gregarious ectoparasitoid that attacks larvae of several species of Lepidoptera. Although there are two genetically different strains within H. hebetor, distribution of the strains has been poorly understood. In 2010, in Thailand, where H. hebetor has been known as a parasitoid of stored grain pests, it was found that H. hebetor attacked Opisina arenosella Walker (Lepidoptera: Oecophoridae), which is an invasive pest of coconut palm. For corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Based on microsatellite loci, Iran and Niger H. hebetor were again clearly separated into two strongly differentiated populations ( F st−ENA( Niger vs Iran) > 0.44). The extent to which all genetic parameters differed led us to wonder whether the two lineages were distinct morphocryptic entities of H. hebetor, possibly geographically associated as reported by Chomphukhiao & co-authors (2018) or even two closely related species although both clustered with H. hebetor sequences. This question remains unanswered until additional samples from Iran can be analyzed.…”
Section: Discussionmentioning
confidence: 91%
“…Based on microsatellite loci, Iran and Niger H. hebetor were again clearly separated into two strongly differentiated populations ( F st−ENA( Niger vs Iran) > 0.44). The extent to which all genetic parameters differed led us to wonder whether the two lineages were distinct morphocryptic entities of H. hebetor, possibly geographically associated as reported by Chomphukhiao & co-authors (2018) or even two closely related species although both clustered with H. hebetor sequences. This question remains unanswered until additional samples from Iran can be analyzed.…”
Section: Discussionmentioning
confidence: 91%
“…xylostella (Arvanitakis et al 2014). On the other hand, recent studies have revealed that the host ranges of idiobiont ectoparasitoids, such as Bracon and Habrobracon species (Braconidae), are narrower than that expected previously (Chomphukhiao et al 2018;Matsuo et al 2016). Host specificity of parasitoids in relation to koinobiosis or idiobiosis will be a challenging issue to be discussed again.…”
Section: Discussionmentioning
confidence: 94%
“…The best characters to discriminate the two species are therefore the ones given in the key: length of antenna to length of head and mesosoma; orientation and length of seta of vertex; length of first flagellar segment of male antenna to length of second flagellar segment; suface structure of metasoma. Chomphukhiao et al (2018) tested for reproductive success and it showed that the two populations (Japan and Thailand) or in other words the two species H. hebetor and H. brevicornis did not reproduce or only produced males. They confirmed the results of Heimpel et al, that the cryptic species aka H. brevicornis is sexually isolated from H. hebetor.…”
Section: H Hebetor)mentioning
confidence: 99%
“…Although H. hebetor and H. brevicornis do perform differently as biological control agents depending on the host. For example, according to Chomphukhiao et al (2018) both species H. hebetor and H. brevicornis attack Corcyra cephalonica and P. interpunctella (Pyralidae), however, H. brevicornis seemed to lay more eggs with a higher adult emergence rate. This confirms the observation of Heimpel et al that that the cryptic species aka H. brevicornis produces more eggs.…”
Section: Biology and Host Rangesmentioning
confidence: 99%
See 1 more Smart Citation